Keberatan Pihak Ketiga Yang Beritikad Baik Terhadap Perampasan Aset Dalam Tindak Pidana Korupsi - Evander (Faculty of Law, Universitas Airlangga, 2024)
Abstract Evidence is an item of crime and one of the important pieces of evidence in uncovering a crime. Evidence is not always owned by the Defendant but is under the control of a third party with good intentions. This action violated the provisions of Article 28H paragraph (4) of the 1945 Constitution where third party property rights were taken by force. To respond to these problems, Article 19 paragraph (2) of the PTPK Law has protected third parties who have good intentions through